ANALISIS FENOMENA THE MONDAY EFFECT PADA RETURN HARIAN SAHAM PERUSAHAAN INDUSTRI PENGOLAHAN YANG TERDAFTAR DI BURSA EFEK INDONESIA PERIODE 2019 - Syofria Meidona; Ilham Multama; Rahmi Saputri (IAIN BATUSANGKAR, 2021)
This type of research is descriptive and empirical studies, because this research explains the phenomenon of The Monday Effect which is based on experimental observations from previous researchers.This study aims to look at the differences in stock returns on Monday to Friday and to prove the Monday Effect phenomenon in the Basic and Chemical Industry companies listed on the Indonesia Stock Exchange in 2019.The population in this study are all companies in the Basic and Chemical Industries listed on the Indonesia Stock Exchange in 2019, namely 78 companies,the sampling method is purposive sampling.The sample in this study were 6 companies that met the criteria.This study uses a different test, the data analysis technique used for H1 is one sample t-test and independent sample t-test for H2.The results of this study indicate that there is no difference between stock returns on Monday to stock returns on Friday, it means that the Monday Effect phenomenon did not occur in the Basic and Chemical Industry companies in the 2019 period.